PEMBUATAN METIL ESTER DARI MINYAK KEMIRI SUNAN DENGAN KEBERADAAN CO-SOLVENT ASETON DAN KATALIS HETEROGEN NATRIUM SILIKAT TERKALSINASI - Muhammad Yusuf Ritonga; Mangunsong Ruben Reinhard Giovani (Jurnal Teknik Kimia USU, 2016)
Methyl ester can be produced from vegetable oil or animal oil through transesterification process. The problem that often arises in the transesterification process is the long reaction time because of oil and alcohol are not mutually dissolve and also separation and purification catalysts are difficult to homogeneous catalysts. The addition of co-solvent may assist the mixing of the reactants and the use of heterogeneous catalysts can overcome the problem of homogeneous catalysts. Sunan candlenut oil contained high free fatty acid (FFA) content of 9.1517% so it needs to be pretreated by esterification so that the raw material has a 1.0538% FFA. The product from this stage was subjected to produce methylester and glycerol. The produced methyl ester on the upper layer was separated from the glycerol and then washed. Effect of various process variables were investigated. The propertiesof methyl ester like methyl ester content, density, viscosity, iodine value, acid value, the content of methyl ester, triglycride(TG), diglyceride(DG) and monoglyceride (MG) was evaluated and was found to compare well with Indonesian Standard (SNI) and European strandart (EN). On this work the best yield condition , was obtain by using amount of catalyst 3% at 40oC, for reaction time 30 minute in presence of 20% co-solvent of the 96,1493 yield methyl ester. The result of this work showed that sunan candlenut oli is very suitable as the feedstock of methyl ester.